Coaching MSMEs through the Business Development Services Program - Panji Putranto; Meiliyah Ariani (PARAHITA : Jurnal Pengabdian kepada Masyarakat, 2020)
The Government pays attention to the development of Micro, Small, Medium Enterprises (MSMEs) to increase competition, develop technology, create diverse markets, increase employment opportunities, production output and the contribution to the country. The government is aware of its importance as a source of poverty reduction, growth in GRDP. Government collaborating with parties expected to increase the enthusiasm of those who have declined. Collaboration between agencies through Business Development Service have long-term goals. Students expected to understand the role of taxes. For university, can be a means of community service and contribute to the institution accreditation standards 7.6 and 7.7. Whereas for SMEs with one hundred target, can improve managerial skills. With the support of E-Commerce, digital training technology transfer, MSMEs can sell through website and manage finance with android. Research Irfan Fatoni, Indah Dewi Nurhayati "Analysis of BDS harmony –Provider (BDSP) with Government Regulations Regarding MSMEs Development in East Java (2014), only discussed the harmony achieved by BDS-P, not cooperation between parties. Community service are carried out by field surveys, interviews with MSMEs in Pondok Melati. BDS carried out in tax workshops, BDS socialization, E-Commmerce, simple bookkeeping, brand image training and bazaar encourages MSMEs to grow, develop. So that small households can prosper independently and reduce the burden of government. By following a year continuous assistance, non-productive can become productive, professional MSMEs. This is evidenced by the formation of MSMEs management with provision of independent equipment following bazaars. Closer to the ideals of MSME villages in Pondok Melati.